2023
DOI: 10.1038/s41392-023-01330-w
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis: pathogenic signaling pathways and therapeutic targets

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disorder that leads to disability and affects more than 500 million population worldwide. OA was believed to be caused by the wearing and tearing of articular cartilage, but it is now more commonly referred to as a chronic whole-joint disorder that is initiated with biochemical and cellular alterations in the synovial joint tissues, which leads to the histological and structural changes of the joint and ends up with the whole tissue dysfunction. Currently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
147
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(231 citation statements)
references
References 530 publications
0
147
0
Order By: Relevance
“…As an important regulator of energy homeostasis, AMPK responds to changes in the ratio of ATP to AMP by regulating metabolic enzymes to promote ATP production and inhibit ATP consumption ( Herzig and Shaw, 2018 ). AMPK is a recognized upstream regulator of PGC-1α, which can directly affect the activity of PGC-1α through phosphorylation ( Yao et al, 2023 ) ( Figure 1 ). Silent information regulator 1 (SIRT1) is a histone deacetylase that maintains cartilage homeostasis by promoting chondrocyte proliferation, differentiation and survival, and upregulating genes important for cartilage function ( Almeida and Porter, 2019 ).…”
Section: Regulatory Pathways and Molecules Of Pgc-1α In Oa Chondrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important regulator of energy homeostasis, AMPK responds to changes in the ratio of ATP to AMP by regulating metabolic enzymes to promote ATP production and inhibit ATP consumption ( Herzig and Shaw, 2018 ). AMPK is a recognized upstream regulator of PGC-1α, which can directly affect the activity of PGC-1α through phosphorylation ( Yao et al, 2023 ) ( Figure 1 ). Silent information regulator 1 (SIRT1) is a histone deacetylase that maintains cartilage homeostasis by promoting chondrocyte proliferation, differentiation and survival, and upregulating genes important for cartilage function ( Almeida and Porter, 2019 ).…”
Section: Regulatory Pathways and Molecules Of Pgc-1α In Oa Chondrocytesmentioning
confidence: 99%
“…In addition, SIRT3 also affects AMPK activity by promoting the expression of liver kinase B1 (LKB1) ( Li et al, 2022 ). LKB1 is the main kinase that catalyzes the process of AMPK activation and energy production, and the activation of AMPK further promotes the expression of PGC-1α ( Yao et al, 2023 ). Forkhead box class O 3 A (FoxO3A) is a transcription factor of the FOXO family, and like PGC-1α, limits cellular oxidative stress by upregulating antioxidant enzymes ( Zhao et al, 2014 ; Almeida and Porter, 2019 ).…”
Section: Regulatory Pathways and Molecules Of Pgc-1α In Oa Chondrocytesmentioning
confidence: 99%
“…The cellular metabolism in IVD and articular cartilage is a coordinated network dynamically modulated at various levels by external stimuli (environmental factors) and resource availability (genetic factors). Although the molecular mechanisms underlying cellular metabolism remain largely unclear, it is widely accepted that apoptosis, ECM disruption, inflammation, and angiogenesis are involved in the development of IDD and OA 8,41,54–56 . Moreover, studies have demonstrated that these biological processes mentioned above are closely associated with PTGR, which is coordianted by RBPs and ribonucleoprotein (RNP) complexes 10,11,13 .…”
Section: Potential Role Of Rna Binding Proteins In Intervertebral Dis...mentioning
confidence: 99%
“…OA is a primary cause of disability that results in cartilage deterioration and joint remodeling. 43 Chronic mild inflammation significantly drives OA, with synovitis exacerbating symptoms, joint issues, and cartilage damage. 44 PDT is a low-invasive method for the treatment of OA with high efficacy and selectivity.…”
Section: Pdt In Oamentioning
confidence: 99%